Professional identity construction of EFL teachers as autonomous learners - Rachmajanti, Sri; Sulistyo, Gunadi Harry; Megawati, Fika; Akbar, Ayu Alif Nur Maharani (Universitas Muhammadiyah Sidoarjo, 2021)
Teacher Professional Development (TPD) is exponential for English teachers to the success of teaching and learning process in the classroom. Teachers with professional identity are deemed to have good quality in teaching. As stipulated by Rodgers & Scott (2008) teachers with professional identity are deemed to have good quality in teaching. The efforts to do this can be accomplished through such ways as participating in conferences, seminars, workshops, and non-degree training, or even pursuing their further studies to master’ s degree and doctorate program. Also, they can conduct research and publish articles. This article is intended to provide evidence how novice, mid-career, and senior EFL teachers construct their identity professionally and autonomously. To arrive at the purpose of the study, an explorative survey was carried out to 129 EFL teachers throughout the Province of East Java via online questionnaire with 37 close-ended items. The findings revealed that (1) EFL teachers, be they junior, mid-career or senior ones involved in the present study, have tried to professionalize themselves via a number of corridors from self-directed ones to the ones imposed by other professional development providers; (2) teachers perceive their professional status and areas in diverse ways, and (3) they have various professional and pedagogical knowledge and skills related to becoming professional EFL teachers. In conclusion, EFL novice, mid-career or senior teachers have manifested their professional identity with a number of corridors as professional autonomous learners. HIGHLIGHTS : Most teachers, especially in the senior and mid-career groups, are committed to improving their English skills. Teachers tend to be more interested in taking part in workshops on ICT-based teaching compared to other themes. Teachers tend to have quite high self-perceptions regarding their level of professionalism, although there is variation between seniority groups.